Improving Students Vocabulary Mastery by Combining Animation Video and Flash Card - Ngabalin, Elsofly Dit Yamtel; Noni, Nurdin; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2024)
This research aimed to investigate the effectiveness of combining animation videos and flashcards in enhancing students' vocabulary at YP PGRI 4 Makassar. A quasi-experimental method was employed with a five-group pre-test and post-test design. The sample consisted of 46 students selected through a total sampling technique. The data analysis revealed a significant difference in students' English vocabulary, as evidenced by t-test values exceeding the critical t-table values for both Class VIIIa (14.099 > 2.160) and Class VIIIb (7.20 > 2.093). These findings indicate that teaching English vocabulary through the combination of animation videos and flashcards effectively improves vocabulary mastery at SMP YP PGRI 4 Makassar. The results of the pre-test and post-test analyses further corroborate this conclusion. The pre-test means scores for both the Experimental and Control classes showed no significant difference (Experiment: 61.85, Control: 60.60, p > .05). However, after the treatment, the post-test means scores revealed a substantial improvement in the Experimental class (84.41) compared to the Control class (78.07), with p-values of .001 for both groups. Therefore, the integration of animation videos and flashcards is a promising method for enhancing students' English vocabulary proficiency.